The Effect of CO2 Partial Pressure on CH4 Recovery in CH4-CO2 Swap with Simulated IGCC Syngas - Ding, Ya-Long; Wang, Hua-Qin; Xu, Chun-Gang; Li, Xiao-Sen (Energies, 2020)
To investigate the influence of CO2 partial pressure on efficiency of CH4-CO2 swap from natural gas hydrates (NGHs), the replacement of CH4 from natural gas hydrate (NGH) is carried out with simulated Integrated Gasification Combined Cycle (IGCC) syngas under different pressures, and the gas chromatography (GC), in-situ Raman, and powder X-ray diffraction (PXRD) are employed to analyze the hydrate compositions and hydrate structures. The results show that with the P-T (pressure and temperature) condition shifting from that above the hydrate equilibrium curve of IGCC syngas to that below the hydrate equilibrium curve of IGCC syngas, the rate of CH4 recovery drastically rises from 32% to 71%. The presence of water can be clearly observed when P-T condition is above the hydrate equilibrium curve of IGCC syngas; however the presence of water only occurs at the interface between gas phase and hydrate phase. No H-2 is found to present in the final hydrate phase at the end of process of CH4-CO2 swap with IGCC syngas.